Impact of Extreme Weather on Construction Projects in Koronadal City, Philippines - Namuag, Lenon; Noval, Joshua Marvin; Flores, El-j; Pagay, Czeska Mae; Delgado, Earl Ian (Journal of Interdisciplinary Perspectives, 2024)
This research investigated the impact of extreme weather on construction projects in Koronadal City. This study aimed to (1) identify the specific types of extreme weather events affecting construction projects; (2) measure the perceived level of impact of extreme weather on construction project timelines, budgetary allocations, labor productivity, equipment performance, and the overall project quality; (3) identify the potential health and safety hazards that might be encountered by individuals in the construction industry; and (4) measure the perceived level of effectiveness of the existing resilience measures employed by construction projects in Koronadal City to mitigate the adverse impact of extreme weather. Data were gathered using survey questionnaires from various respondents, including engineers and construction workers. A survey involving 177 respondents identified frequent weather-related challenges, with heat waves being the most prevalent, followed by heavy rainfall and less frequent occurrences of floods, tropical cyclones, and tornadoes. The study also explored the impact of extreme weather on the health and safety of construction personnel, highlighting issues such as physical strain, heat-related illnesses, and increased risks of accidents due to adverse weather. The findings indicate significant disruptions to project timelines and financial planning, with a considerable majority reporting that extreme weather necessitates project management and budgeting adjustments. Furthermore, the study reveals the effectiveness of current resilience measures, including providing adequate hydration and regular breaks in shaded areas and utilization of adequate rest breaks, rotating tasks, and employee wellness programs. This paper underscores the urgent need for enhanced adaptive measures and more efficient risk management strategies to ensure the safety and effectiveness of construction practices in regions vulnerable to extreme weather.